2018
DOI: 10.1177/0022034517746987
|View full text |Cite
|
Sign up to set email alerts
|

EZH2 Impairs Human Dental Pulp Cell Mineralization via the Wnt/β-Catenin Pathway

Abstract: The enhancer of zeste homolog 2 (EZH2) is a catalytic subunit of PRC2 (polycomb repressor complex 2). It mediates gene silencing via methyltransferase activity and is involved in the determination of cell lineage. However, the function of EZH2 and the underlying mechanisms by which it affects the differentiation of human dental pulp cell (hDPC) have remained underexplored. In this research, we found that EZH2 expression decreased during the mineralization of hDPCs, with attenuated H3K27me3 (trimethylation on l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 34 publications
0
36
0
Order By: Relevance
“…β‐catenin expression was up‐regulated during the odontoblastic differentiation of DPSCs (Han et al ). Activating Wnt/β‐catenin signalling either by WNT7B or by depleting the enhancer of zeste homolog 2 (EZH2) similarly promoted DPSC differentiation (Li et al , Lv et al ). In contrast, β‐catenin knockdown inhibited DPSC odontoblastic differentiation (Han et al ).…”
Section: Discussionmentioning
confidence: 99%
“…β‐catenin expression was up‐regulated during the odontoblastic differentiation of DPSCs (Han et al ). Activating Wnt/β‐catenin signalling either by WNT7B or by depleting the enhancer of zeste homolog 2 (EZH2) similarly promoted DPSC differentiation (Li et al , Lv et al ). In contrast, β‐catenin knockdown inhibited DPSC odontoblastic differentiation (Han et al ).…”
Section: Discussionmentioning
confidence: 99%
“…When β -tricalcium phosphate/DPSCs transfected with siEZH2 are transplanted under the skin of nude mice, the formation of mineralized tissue is improved. Further, the results of a CHIP assay suggested that EZH2 downregulates the expression of β -catenin by increasing the levels of H3K27me3 on the promoter region of β-catenin , eventually suppressing the Wnt/ β -catenin signaling pathway that is critical for odontogenic differentiation [ 110 ]. EZH2 is also related to the proliferation, osteogenic differentiation, and inflammatory response of DPSCs.…”
Section: Epigenetic Mechanisms In Dpscsmentioning
confidence: 99%
“…We performed in vivo bone formation analysis using subcutaneous transplantation as described previously [21]. In brief, we soaked beta-tricalcium phosphate (β-TCP) blocks (5 mm × 5 mm × 2 mm) in OM for 30 min at 37°C.…”
Section: In Vivo Bone Formation Of Hdpcsmentioning
confidence: 99%